MANAJEMEN PENYIDIKAN ANTARA PENYIDIK POLRI KE JAKSA PENUNTUT UMUM DALAM PENYELESAIAN BERKAS PERKARA - Indra Mardiana (Faculty of Social and Political Science, 2015)
The purpose of this study is to analyze the management of investigation in the settlement of case files from investigators to prosecutors. This study uses statute approach (statute approach) and conceptual approach (conceptual approach). Data analysis techniques in this study using descriptive analysis that describes the legal preposition or non-legal events. The result of the research shows that the management of investigation in the settlement of the case file of the Police Investigator to the Prosecutor begins with the investigation process of alleged criminal act based on the report or complaint submitted by the society, which then from the investigation result is increased into investigation in order to find the criminal incident. The result of the investigation shall be submitted to the Public Prosecutor for the determination of the suitability of the Case File may proceed to the pre prosecution process for the creation of the indictment against the suspect. If the Case File is deemed unfeasible to proceed based on the analysis of the Public Prosecutor, then the Case File shall be returned to the investigator to be fulfilled. In the process of investigation, the benchmark management of the investigation in the handling of criminal offenses is the Criminal Procedure Code. each case file from Police Investigator to Prosecutor is often constrained by the discretion of every Police and Prosecutor institution so that it can slow down the fulfillment of the elements of the offense that it wants to suspect to the Suspects or to find any criminal incidents.